Clinical utility of cytomegalovirus urine cultures for ophthalmic care in patients with HIV. Issue 9 (September 1996) - Gellrich, M M; Baumert, E; Rump, J A; Vaith, P; Hufert, F T; Hansen, L L
Abstract : BACKGROUND: The utility of cytomegalovirus (CMV) urine cultures was checked in patients with HIV (a) to identify those at risk for CMV retinitis and (b) to guide clinical decisions on treatment and prophylaxis of CMV retinitis. METHODS: HIV infected patients were tested for CMVuria by shell vial cell cultures. The prevalence of CMVuria was related to CD4 count, HIV risk group, and time before and after diagnosis of CMV retinitis. RESULTS: A total of 639 shell vial cell cultures were obtained from 266 HIV infected ophthalmic patients. Only 4% of all patients with a CD4 count > 400 x 10(6)/l shed CMV in their urine compared with 42% with a CD4 count < or = 50 x 10(6)/l. Twenty three of 25 patients with CMV retinitis had a CD4 count < or = 50 x 10(6)/l. Among 130 patients with a CD4 count < or = 50 x 10(6)/l (a) those who were CMVuric had a nearly sevenfold risk (p < 0.0001) of developing CMV retinitis (35%) compared with those who did not shed CMV in their urine (5%), and (b) CMVuria and CMV retinitis were more frequent in homosexuals (58%/25%) than in intravenous drug users (23%/15%). More than 1 year before diagnosis of CMV retinitis 18% of patients were CMVuric compared with 83% of patients who were CMV culture positive in the last 3 months. CMVuria under virustatic maintenance therapy is associated with worsening of retinitis in two thirds of cases. CONCLUSION: Ophthalmic screening of patients with HIV should include those with a CD4 count < or = 50 x 10(6)/l and focus on the subgroup with additional CMVuria. Screening of other patients can be dropped without undue risk in order to spare AIDS patients unnecessary hospital visits. CMVuria as a single finding, however, does not justify antiviral prophylaxis of CMV retinitis.